Proyecto de factibilidad para la implementación de un asadero de pollos en la parroquia Chantaco, cantón Loja, provincia de Loja - Caraguay Loarte, Gladys Carmita (2015)
This research work prior to obtaining the degree of Engineer in Business Administration is aimed at developing a feasibility project for the implementation of a steakhouse chicken in the Parish of Chantaco province of Loja; this investment proposal seeks to provide a possible solution to the problems caused by lack of jobs as well as provide a place where you can vary the existing dining at this parish. This has been proposed as main objective to determine the feasibility of implementing a steakhouse chicken Chantaco Parish in the Province of Loja; after performing the respective financial market research, technical, and financial evaluation. To develop materials and methods were used techniques and instruments listed below were applied. The same inductive method that allowed the and market research, technical, administrative, financial, was used. For market research market characteristics such as supply and demand, and other variables such as price competition, etc. are identified. A statistical sample whose size and sample selection was sufficient to obtain 7 reliable results was used, which led to highlight the application of 165 surveys. It should be noted that in determining the sample was taken as the basis of the 2010 population census, ie the total population of the parish Chantaco Families, which is 280 families. The results are: The potential demand for this product represents 91% of the families, ie 280 Child 2014; while the actual demand represented (93%) persons in their diet consumed roast chicken and effective demand is represented by 100% of Families, Child ie 280 for the same year. After conducting an analysis of firm size, organization, geographic location, project engineering, physical infrastructure, production process, etc.Technical study was conducted,the same will choose the best alternative for opening this business.The company will be located in a corner of the Parish of San Jose Av Chantaco. overall installed capacity working 350 days of the year will be14000 chickens,the overall spare capacity laboring six days, offering 30 chickens a day will be7800 chickens a year,working with direct labor of a chef,kitchen assistant and two waiters; The project is estimated to a useful life of 5 years. For the continuation of the project is vital the exact location of each account in the budget, in order the amount of capital to open the business. For implementation and opening of this organization investing $ 16,524.83 8 is needed and have an own financing 47.87% equivalent to $ 7,910.43; and an outer of 52.13% amounting to $ 8,614.00 financed capital acquired Banco de Fomento productive credit advantage that this entity provides. It is also necessary to know the financial viability that has the project in terms of recovery of invested capital, the ability to pay claims and to understand and weigh the effects that the credit would have on its liquidity; this is necessary for a financial project evaluation, they reflect the financial indicators of the project are positive. With a projection of 5 years, a net present value of $ 50,336.29 and an IRR of 79.95% is obtained, giving a cost of $ 0.22 for every dollar invested benefit ratio, the investment will be recovered in 1 year, 8 months and 1 days. Finally you get to establish findings and recommendations, as the financial indicators are positive for investors of this project, it is advisable to invest and start it.